Demand re-registration for PCS database restoration - Haas, ZJ; Lin, YB (My University, 2000)
In a Personal Communications Services (PCS) network, mobility databases such as Home Location Register (HLR) and Visitor Location Register (VLR) are utilized to support mobility management for Mobile Stations (MSs). If the location databases fail, the location information loss or corruption will seriously degrade the service offered to the subscribers. In this paper, we propose a new VLR failure recovery scheme called demand re-registration. In this scheme, the VLR broadcasts a re-registration request to all MSs after the VLR failure. When an MS receives the re-registration request, it sends a registration message to the VLR to recover the location record. Since all MSs will re-register after receiving the broadcasting request, traffic jam (and thus collisions) may occur. If a collision occurs, then the involved MSs must re-send the registration messages. This paper studies the performance of demand re-registration by investigating how effectively the re-registration can recover the location record for an MS before the first MS call termination occurs. Our results indicate that demand re-registration can effectively recover VLR failure.